Effects of mineral fertilization on fruit quality in drip-irrigated Marselan grape (Vitis vinifera) - Shi, Xingyun; Xu, Shanshan; Li, Qiang; He, Cai; Wang, Duowen; zhang, Qinde; Mu, Desheng; Wang, Lixin (The Indian Journal of Agricultural Sciences, 2020)
Top quality of grape (Vitis vinifera L.) berries is essential for producing delicious and customer-favorite wine. Thus, the optimal application of mineral fertilizers is important and necessary. Here, a standard drip-irrigation protocol with five different mineral fertilizer (F) treatments- C0 kg/ha (control), F1 245 kg/ha, F2 490 kg/ha, F3 735 kg/ha and F4 980 kg/ha were laid out in a split-plot design to evaluate their effects on grapevine factors which included shoot growth, berry weight and size, and berry sugar, acid, phenolics and volatiles. The experiment was conducted at the Wuwei Academic Forest Science Center during 2017. The results showed that all fertilizer applications significantly promoted shoot growth. Fruit weight and size increased under F2 and F3 treatments. In addition, soluble solids and reducing sugars grew up under F3 treatment. However, sugar-acid ratios did not differ significantly among all F treatments but phenolic and tannin levels were increased under F3 treatment, as were anthocyanin levels under F1, F2 and F3 treatments. A total of 83 different aroma components were identified in all the F treatments. These were clustered into seven groups. The total amount of aroma components tended to increase, then to decrease with increasing rates of fertilization (from C to F4).The results indicate that mineral fertilizer application has complex effects on the berry quality factors that were evaluated.